MAXIMUM NUMBER OF REPETITIONS, TOTAL WEIGHT LIFTED AND NEUROMUSCULAR FATIGUE IN INDIVIDUALS WITH DIFFERENT TRAINING BACKGROUNDS - Valeria Panissa; Raymundo Azevedo Neto; Ursula Julio; Leonardo Andreato; Claudio Pinto e SIlva; Emerson Franchini (Termedia Publishing House, 2013)
The aim of this study was to evaluate the performance, as well as neuromuscular activity, in a strength task in subjects with different training backgrounds. Participants (n = 26) were divided into three groups according to their training backgrounds (aerobic, strength or mixed) and submitted to three sessions: (1) determination of the maximum oxygen uptake during the incremental treadmill test to exhaustion and familiarization of the evaluation of maximum strength (1RM) for the half squat; (2) 1RM determination; and (3) strength exercise, four sets at 800of the 1RM, in which the maximum number of repetitions (MNR), the total weight lifted (TWL), the root mean square (RMS) and median frequency (MF) of the electromyographic (EMG) activity for the second and last repetition were computed. There was an effect of group for MNR, with the aerobic group performing a higher MNR compared to the strength group (P = 0.045), and an effect on MF with a higher value in the second repetition than in the last repetition (P = 0.016). These results demonstrated that individuals with better aerobic fitness were more fatigue resistant than strength trained individuals. The absence of differences in EMG signals indicates that individuals with different training backgrounds have a similar pattern of motor unit recruitment during a resistance exercise performed until failure, and that the greater capacity to perform the MNR probably can be explained by peripheral adaptations.